2013
DOI: 10.1007/s12288-013-0244-5
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Fludarabine, High Dose Cytosine Arabinoside with Granulocyte Colony Stimulating Factor (FLAG) Protocol as Salvage Therapy for Refractory/Relapsed Acute Leukemias in Adult Iraqi Patients

Abstract: Refractory/relapsed acute leukemia has always been a challenging problem for hematologist. Over the past decade emphasis has been made in the development of regimens containing fludarabine, combined with cytosine arabinoside for the treatment of refractory/relapsed acute leukemias. The aim of this study is to evaluate the efficacy and toxicity of the combination of fludarabine, high dose cytarabine, and granulocyte colony stimulating factor in refractory relapsed cases of acute leukaemia, a prospective study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The suppression to host immunity of CY is replaced by fludarabine. Recently, some comparative trials showed that FLAG regimens with or without IDA /Mito produced an excellent effect in children with relapsed/refractory acute leukemia, and it could be recommended as therapeutic options prior to HSCT [ 16 22 ]. The introduction of FLAG and CLAG with IDA /Mito into the conditioning regimen is undoubtedly beneficial to the elimination of residual leukemia with acceptable toxicity, which is one of the main factors to reduce the recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…The suppression to host immunity of CY is replaced by fludarabine. Recently, some comparative trials showed that FLAG regimens with or without IDA /Mito produced an excellent effect in children with relapsed/refractory acute leukemia, and it could be recommended as therapeutic options prior to HSCT [ 16 22 ]. The introduction of FLAG and CLAG with IDA /Mito into the conditioning regimen is undoubtedly beneficial to the elimination of residual leukemia with acceptable toxicity, which is one of the main factors to reduce the recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…High dose Ara-C combined with other regimens are available, such as FLAG, FLAG-IDA etc [16,22]. FLAG is commonly used salvage regimen which is believed to produce a CR rate ranging from 39.1-83%, yet followed by severe myelosuppression and related infection [8,23]. For resistant and relapsed patients, some clinical center applied FLAG-IDA regimen, which combined idarubicin with FLAG regimen, while the CR rate ranges from 20-42% and the side effect including pancytopenia, life-threatening infections and neurological toxicity are observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Major complications encountered were anemia, fever, bleeding, mucositis, and bacterial infections. 41 …”
Section: Chemotherapymentioning
confidence: 99%